Efficacy of Accommodation Strategies for Students with Disabilities in Undergraduate Exit Exams: A Systematic Literature Review - Teshome, Samson Worku (International Journal of Humanities, Education, and Social Sciences, 2025)
Exit exams in higher education function as critical evaluative tools to verify that students satisfy academic criteria prior to graduation. However, the integration of disability accommodations within these assessments remains insufficiently explored, raising concerns about equity and accessibility. This systematic review synthesizes current literature on the intersection of exit exams and disability, focusing on the challenges, strategies, and outcomes experienced by students with disabilities. Employing the PRISMA framework, 31 studies were analyzed, uncovering notable gaps in standardized accommodations and limited evidence regarding the long-term impacts of these exams on students with disabilities. While individualized accommodations, such as extended time, alternative formats, and flexible scheduling demonstrate potential to enhance fairness, systemic barriers persist, including inconsistent implementation and resource constraints. The review emphasizes the application of universal design principles to develop inclusive assessments that serve all students. Furthermore, it highlights the necessity of educator training and policy reforms to mitigate disparities. Key findings indicate that although accommodations improve immediate exam performance, their effects on long-term academic and career outcomes warrant further investigation. This study contributes to advancing educational equity by providing actionable recommendations for policymakers, educators, and researchers aimed at fostering more inclusive assessment practices.